Relationships between otolith dimension, age and somatic growth of Anguilla bicolor bicolor (McClelland 1844) collected from northwest of Peninsular Malaysia - Ismail, Muhammad Faiz; Azmai, Mohammad Noor Amal; Shohaimi, Shamarina; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir; Ab Ghani, Nurul Izza (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study reports the relationships between otolith dimension, age and somatic growth of Anguilla bicolor bicolor in northwest of Peninsular Malaysia. The length–weight relationship of the eels was recorded at W = 0.0001L3.659. There were significant relationships between all of the equations established between selected otolith dimension, age and somatic growth. The equations derived from this study could help in future study on population dynamics, stock assessment and conservation of this species. This is the first study of these relationships for A. b. bicolor in this country.